THE EFFECT OF MARKETING CHANNELS AND PACKAGING ON BUSINESS SUCCESS IN STANDARD BUSINESSES IN THE CITY OF LHOKSUMAWE: (Case Study on Internet Data Package Merchants) - Adi Wijaya, Siswoyo; Hanum, Syarifah; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2021)
The results of this study show. (1) The constant value (a) of 6.253 indicates the magnitude of the Business Success Variable (Y) if the Marketing Channel Variable (X1) and the Packaging variable (X2) are equal to zero. (2) It can be seen that the adjusted R square value is 0.308 or 30.8%. This shows that the Marketing Channel Variable (X1) and Packaging Variable (X2) can explain the Business Success Variable (Y) of 30.8%, the remaining 69. 2% (100% - 30.8%) is explained by other variables outside this research model. (3)Testing the first hypothesis, it can be seen that tcount (0,-404) < ttable (-2.004), as well as the significance value of 0,689 > 0.05, it can be concluded that the hypothesis first rejected, it meansVariable Marketing channel(X1) has no significant effect on Variable Business Success (Y). (4) Testing the second hypothesis, it can be seen that tcount (3,934) > ttable (2.004), and the significance value is 0.000 <0.05, it can be concluded that the second hypothesis is accepted, meaning thatVariable Packaging (X2) has a significant effect on the Business Success Variable (Y). (5) Testing the third hypothesis, it can be seen that Fcount (7,894) > Ftable (3.33), and a significance value of 0,002<0.05, it can be concluded that the third hypothesis is accepted, meaning that Variable Marketing channel(X1), Variable Packaging (X2) has a significant effect simultaneously (simultaneously) on the Variable Business Success (Y).